Homosexuality: out of the educational closet - Walter M. Mathews (Educational Considerations, 1976)
This article confronts the issue of homosexuality as it relates to the school. The treatment that educators have generally given to homosexuality reflects an unfortunate potpourri of prejudice and misinformation that is shared by a great portion of the public. This article provides basic information to educators who have not been in a position to objectively consider the issue of homosexuality and the school, and attempts to nudge educators toward further fact-finding and consideration of the problems so that they foster change in their schools and communities.